Now or never : thirty-one on the run - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel, 2024)
With her personal life in turmoil, New Jersey bounty hunter Stephanie Plum navigates danger and intrigue in a high-stakes case that could change her life.